2021
DOI: 10.1007/s12144-021-02352-9
|View full text |Cite
|
Sign up to set email alerts
|

Can acute resistance exercise facilitate episodic memory encoding?

Abstract: Research has shown benefits of physical exercise on memory performance when carried out before or after a memory task. The effects of concurrent physical exercise and particularly resistance exercise are still inconclusive. The current study investigates the influence of resistance exercise with two intensities (fast and slow squats) on performance in a wordlist learning task using a within-subject design. Sport students (N = 58, Mage = 23 years; 26 women) were trained in a mnemonic technique to encode word li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The highest MoL costs in previous studies occurred when encoding took place while tracing symbols (about 40% in young adults; Amico and Schaefer, 2020), while walking on complex tracks with obstacles (about 40% in older adults; Li et al, 2000Li et al, , 2001, or while doing squats with every second word (about 35% in young adults; Amico et al, 2023). The cognitive costs of the current studies are considerably higher than that, with about 60% during fast rowing in study 1 and almost 80% for the relatively less-experienced holders of yellow belts in study 2 (see Figure 4).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The highest MoL costs in previous studies occurred when encoding took place while tracing symbols (about 40% in young adults; Amico and Schaefer, 2020), while walking on complex tracks with obstacles (about 40% in older adults; Li et al, 2000Li et al, , 2001, or while doing squats with every second word (about 35% in young adults; Amico et al, 2023). The cognitive costs of the current studies are considerably higher than that, with about 60% during fast rowing in study 1 and almost 80% for the relatively less-experienced holders of yellow belts in study 2 (see Figure 4).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies had used MoL memory encoding in combination with different motor tasks (while walking on easy and complex narrow tracks with and without obstacles: Li et al, 2000Li et al, , 2001; while balancing on an ankle-disc board: Schaefer et al, 2008; while rotating a fidget spinner, doodling, or tracing: Amico and Schaefer, 2020; while doing fast or slow squats: Amico et al, 2023). Participants were children, young, or older adults.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Amico et al [ 71 ], muscle contractions while squatting may lead to the activation of the LC via the muscle spindle pathway . During muscle contraction, muscle spindles become active and send action potentials to the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…During muscle contraction, muscle spindles become active and send action potentials to the brainstem. These ascending signals ensure activation of the LC [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, acute resistance exercise involving knee extension/flexion during the consolidation period of an episodic memory task has demonstrated positive effects, particularly when the memory task has affective valence [84]. However, these effects were not observed when exercise was conducted during the consolidation period [85] or when the exercise intensity was vigorous [86]. Moreover, studies utilizing a research design with four experimental groups have not shown exercise before encoding to be significantly superior to the control group [87].…”
Section: Clinical Studies About Exercise and Episodic Memorymentioning
confidence: 99%